PENGARUH FAKTOR MIKROEKONOMI TERHADAP HARGA SAHAM LQ45 DI BURSA EFEK INDONESIA - Ninin Non Ayu Salmah (Jurnal Media Wahana Ekonomika, 2013)
This research aimed to recognize the influence of microeconomic factors which are price earning ratio, debt to equity ratio, and return on equity towards the price of stock Index LQ45 at the Indonesian Stock Exchange. The population of this research was all go public companies which have been noted into the group of LQ45 share at the Indonesian Stock Exchange in 2008 until 2012 and the sample was the companies which was actively noted in LQ45 index during the research period. The technique to analyze the data was descriptive-quantitative by using determination coefficient tool, doubled-linear regretion after doing classic assumption test. The examination of hypothesis was done towards the submission of hypothesis such as the influence of debt to equity ratio, return on equity, and price earning ratio towards the price of LQ45 index stock simoultaneously and partially. The result showed that price earning ratio, debt to equity ratio, and return on equity simoultaneously and significantly affected the price of stock. The research also resulted the price earning ratio and return on equity partially and significantly influenced the price of stock meanwhile the debt to equity ratio did not affected significantly to the price of stock of companies noted in LQ45 index at the Indonesian Stock Exchange. Keywords: price earning ratio, debt equity ratio,retuirn on equity, price of stock